Pengaruh Pemberian Kompos Paitan (Tithonia Diversifolia) dan Nanopartikel Cangkang Telur Terhadap Pertumbuhan Dan Produksi Bawang Merah (Allium Ascalonicum) - Ridho Ari Kusuma; Suswati Suswati; Erwin Pane (Jurnal Ilmiah Pertanian ( JIPERTA), 2021)
This study aims to determine the effect of giving Paitan (Tithonia diversifolia) compost, Eggshell Nanoparticles, and a combination of giving Paitan (Tithonia diversifolia) compost and eggshell nanoparticles simultaneously on growth and production of Shallots (Allium ascalonicum). This study used a factorial randomized block design (RBD) with two research factors, namely giving paitan compost (P0 = without applying fertilizer; P1 = 0. 5 kg / plot; P2 = 1 kg / plot; P3 = 1. 5 kg / plot) and giving egg shell nanoparticles (N0 = without giving nanoparticles; N1= 1 g / plot; N2 = 1. 5 g / plot; N3 = 2 g / plot), repeated 2 times.Â  eggshell nanoparticles had a very significant effect on plant height at the age of 2. 4 and 5 WAP, on the number of leaves at 3 WAP, and had a significant effect on plant height at 3 and 6 WAP, on the number of leaves 2 and 4 WAP but not significant effect on plant height 7 and 8 WAP, on the number of leaves at 5 to 8 WAP, and other parameters. The combination effectiveness of paitan compost and eggshell nanoparticles had a very significant effect on the number of leaves at 2 and 3 WAP, and had a significant effect on the number of leaves at 4 WAP but had no significant effect on plant height at 2 to 8 WAP, for the number of leaves at 5 to 8 MST and on other parameters